SOME REMARKS ON TWO MULLINEUX’S PARTITIONS - Mahmood, Ammar; ghanem, Esraa (Iraqi Journal of Science, 2024)
Mullineux in 1979 presented two researches taking in them some special methods ofthe partition theory, as he represented a kind of a special partition a mathematical sensewithout any proof of it. Fayers in 2009 presented it with its conditions adding anothertype pf partition and called the two partitions of Mullineux. The main aim of our work isto find a suitable partition for the equivalence of these two partitions, where thisequivalence is not always occurred.